Antifungal Properties of Chenopodium ambrosioides Essential Oil Against Candida Species - Gerard Vilarem; Pierre Tane; Jules Roger Kuiate; Jean De Dieu Tamokou; Paul Keilah Lunga; Marie Stéphanie Goka Chekem; Muriel Cerny (MDPI AG, 2010)
The essential oil of the aerial part (leaves, flowers and stem) of Chenopodium ambrosioides was obtained by hydrodistillation and its chemical composition analyzed by GC and GC/MS, which permitted the identification of 14 components, representing 98.8% of the total oil. Major components were α-terpinene (51.3%), p-cymene (23.4%) and p-mentha-1,8-diène (15.3%). The antifungal properties of this essential oil were investigated in vitro by the well diffusion and broth microdilution methods. The in vitro antifungal activity was concentration dependent and minimum inhibitory concentration values varied from 0.25 to 2 mg/mL. The in vivo antifungal activity was evaluated on an induced vaginal candidiasis rat model. The in vivo activity of the oil on mice vaginal candidiasis was not dose-dependent. Indeed, all the three tested doses; 0.1%, 1% and 10% led to the recovery of mice from the induced infection after 12 days of treatment. The effect of the essential oil on C. albicans ATCC 1663 fatty acid profile was studied. This oil has a relatively important dose-dependent effect on the fatty acids profile.